1986
DOI: 10.1038/clpt.1986.134
|View full text |Cite
|
Sign up to set email alerts
|

Nifedipine: Kinetics and hemodynamic effects in patients with liver cirrhosis after intravenous and oral administration

Abstract: The pharmacokinetics and hemodynamic effects of nifedipine were studied in patients with liver cirrhosis and in age-matched healthy control subjects. In a randomized order each subject received nifedipine by intravenous infusion (4.5 mg in 45 minutes) and as a tablet (20 mg). After intravenous nifedipine patients had a longer elimination t1/2 (420 +/- 254 vs. 111 +/- 22 minutes; P less than 0.01), a greater volume of distribution (1.29 +/- 0.60 vs. 0.97 +/- 0.42 L/kg), and a lower systemic clearance (233 +/- 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0
1

Year Published

1987
1987
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(46 citation statements)
references
References 8 publications
4
40
0
1
Order By: Relevance
“…However, others have reported that cirrhosis increases the bioavailability of orally administered CYP3A substrates. 20,22 Cirrhosis produced an increase from 16% to 37% in the bioavailability of isradipine 22 and an increase from 51% to 90% in the bioavailability of nifedipine. 20 However, almost half of the cirrhotic patients in both of these studies had undergone a previous portosystemic shunt surgery.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…However, others have reported that cirrhosis increases the bioavailability of orally administered CYP3A substrates. 20,22 Cirrhosis produced an increase from 16% to 37% in the bioavailability of isradipine 22 and an increase from 51% to 90% in the bioavailability of nifedipine. 20 However, almost half of the cirrhotic patients in both of these studies had undergone a previous portosystemic shunt surgery.…”
Section: Figmentioning
confidence: 99%
“…20,22 Cirrhosis produced an increase from 16% to 37% in the bioavailability of isradipine 22 and an increase from 51% to 90% in the bioavailability of nifedipine. 20 However, almost half of the cirrhotic patients in both of these studies had undergone a previous portosystemic shunt surgery. When we reanalyzed the published data separately for the effects of cirrhosis and shunting, we found that the F PO of isradipine 22 in patients with portosystemic shunts was 0.46 Ϯ 0.14, and in cirrhotic patients without shunts, this value had dropped to 0.28 Ϯ 0.14.…”
Section: Figmentioning
confidence: 99%
“…CYP 3A4 can metabolize more than 120 kinds of drugs and participates in 60% of clinical drug metabolisms to different degrees; 40 to 50% of phase I drug metabolisms are performed by CYP 3A4 (McKinnon et al, 1995;Nelson et al, 1996). Patients with liver disease show different degrees of reduced CYP 3A4 expression and weakened CYP 3A4 activity (Huet and Villeneuve, 1983;Kleinbloesem et al, 1986;Lown et al, 1992;Chalasani et al, 2001;Yang et al, 2003;Horiike et al, 2005). GST constitutes one part of the cell's own defenses to block multiple endogenous and environmental toxic compounds, and protects macromolecules from active electron affinity substance attacks (Strange et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Matsuo et al demonstrated that there is a correlation between the CL tot of cyclosporine and the grade severity of liver disease by Child-Pugh classification in patients with hepatitis. 12) However, it is not easy to utilize these approaches to determine the degree of residual hepatic metabolizing ability in patients, as is also the case with creatinine clearance in patients with renal failure.…”
Section: )mentioning
confidence: 99%
“…[8][9][10][11] Matsuo et al demonstrated that there is a correlation between the CL tot of cyclosporine and the grade severity of liver disease by Child-Pugh classification in patients with hepatitis.…”
mentioning
confidence: 99%